Effects of ultrasonic surface mechanical attrition treatment on microstructures and mechanical properties of high entropy alloys. (February 2018) - Tsai, M.T.; Huang, J.C.; Tsai, W.Y.; Chou, T.H.; Chen, Chin-Fu; Li, T.H.; Jang, J.S.C.
Abstract: Most high entropy alloys (HEAs) are cast to form single phase solid solution. Their hardness and strength at room temperature under the as-cast condition are typically lower than expectation. In the research, the ultrasonic surface mechanical attrition treatment (SMAT) is conducted on the surface of two HEAs, FeCoNiCrMn and FeCoNiCrMn-Al, to upgrade their room temperature surface characteristics. By proper SMAT multiple paths, the grain size can be reduced from ∼50 μm down to ∼0.1–1 μm, the hardness increased from ∼2.5–5.0 GPa up to ∼5.0–8.5 GPa, and the tensile strength and elongation can be nearly doubled. The gradient refined and strengthened surface layers are demonstrated to appreciably upgrade the HEA performance. The strengthening mechanisms and superposition rules are established and are compared well with the experimental measurements. Graphical abstract: Highlights: The ultrasonic surface mechanical attrition treatment (SMAT) is conducted on two HEAs. The grain size can be reduced to ∼0.1–1 μm and the hardness and strength can be doubled. The gradient refined and strengthened surface layers can upgrade the HEA performance.